The accuracy of long-term real estate valuations - Rainer Schulz; Markus Staiber; Martin Wersing; Axel Werwatz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
By using a unique data set of single-family house transactions, we examine the accuracy of the cost and sales comparison approach over different forecast horizons. We find that sales comparison values provide better long-term forecasts than cost values if the economic loss function is symmetric. A weighted average of both sales comparison value and cost value can reduce this loss even further. If the economic loss function is asymmetric, however, cost values might provide better long-term forecasts.
Keywords: C52; C53; 330; prediction accuracy; mortgage underwriting; risk management; Immobilienbewertung; Prognoseverfahren; Hypothek; Theorie; Berlin